Development of High‐Drug‐Loading Nanoparticles. Issue 9 (31st August 2020) - Liu, Yun; Yang, Guangze; Jin, Song; Xu, Letao; Zhao, Chun‐Xia
Abstract: Formulating drugs into nanoparticles offers many attractive advantages over free drugs including improved bioavailability, minimized toxic side effects, enhanced drug delivery, feasibility of incorporating other functions such as controlled release, imaging agents for imaging, targeting delivery, and loading more than one drug for combination therapies. One of the key parameters is drug loading, which is defined as the mass ratio of drug to drug‐loaded nanoparticles. Currently, most nanoparticle systems have relatively low drug loading (<10 wt%), and developing methods to increase drug loading remains a challenge. This Minireview presents an overview of recent research on developing nanoparticles with high drug loading (>10 wt%) from the perspective of synthesis strategies, including post‐loading, co‐loading, and pre‐loading. Based on these three different strategies, various nanoparticle systems with different materials and drugs are summarized and discussed in terms of their synthesis methods, drug loadings, encapsulation efficiencies, release profiles, stabilities, and their applications in drug delivery. The advantages and disadvantages of these strategies are presented with an objective of providing useful design rules for future development of high‐drug‐loading nanoparticles. Abstract : Loaded up : This Minireview presents an overview of recent research on developing nanoparticles with high drug loading (>10 wt%) from the perspective of synthesis strategies, including post‐loading, co‐loading, and pre‐loading. Based on these three different strategies, various nanoparticle systems with different materials and drugs are summarized, and the advantages and disadvantages of these strategies are discussed to provide useful design rules for the future development of high‐drug‐loading nanoparticles.